Water Resources Management in Practices at National Pingtung University of Science and Technology Campus - Chang, Chin-Lung; Shih, Vincent Ru-Chu; Tsai, Meng-Hao (Journal of Sustainability Perspectives, 2023)
NPUST was the top Taiwan university for the 9th consecutive year on the UI GreenMetric World University Ranking, and placed 27th out of 1,050 schools from 85 countries. This achievement is the result of our commitments to sustainable development. NPUST has been building green transportation for carbon and air pollution reduction, green energy system for effective use of electricity generated by renewable energy, and campus waste water recycling system for the goal of zero discharge. We also implement policies on waste reduction and waste sorting and recycling, as well as encourage planting in school campus. The practice of water resources management is crucial in various aspects that contribute to this sustainable campus. The sustainable management strategies include water consumption management, water conservation and water saving, and water recycling management. In this paper, we are going to share our practical experience in waste water treatment, recycling system set-up, waste water reuse, sustainable development for water resources and how we implement the policies on water saving at campus and spread water resources knowledge. The information is provi